Kajian Preferensi Stakeholders terhadap Bangunan Hijau di Lanskap Perkotaan Berbasis Social Media Data (SMD) - Saputri, Ira Maya; Fatimah, Indung Sitti; Kaswanto, Regan Leonardus (http://arl-faperta.ipb.ac.id/, 2025)
Green building is a solution to reduce the impact of climate change originating from the life cycle of buildings. Stakeholders' understanding greatly affects the success of green building implementation in the urban landscape. This research aims to determine the preferences of stakeholders toward green building. Preferences will be used to develop recommendations for green building practices that are potentially implemented in Depok City, West Java. This research uses social media analysis. Social media data was collected from Instagram owned by government agencies, communities, educational institutions, the private sector, and the media. Preferences were identified using topic modeling analysis. Recommendations were developed through a literature study based on the results of preference studies. The preference analysis generated one topic with the keyword “water” being discussed by the community. The green building categories closest to the results of preference analysis are appropriate site development, water conservation, and building environment management because they have objectives and impacts related to water. Green building design concepts can be applied to the landscape. Based on its purpose, the appropriate site development category, which include landscaping the site and managing rainwater runoff criteria, can be designed using landscape systems. One option for green building design concepts in the landscape and related to water supply is rain gardens. The rain garden practice option is expected to increase stakeholders' understanding of the green building concept in Depok City.